2005
DOI: 10.1021/ja0558387
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control of Self-Assembled Nanofibers by Artificial β-Sheet Peptides Composed of d- or l-Isomer

Abstract: A novel method for the control of peptide self-assembly has been developed by using synthetic triblock-type beta-sheet peptides composed of l- or d-amino acid, 1L and 1D, as building blocks. The peptides 1L and 1D self-assemble into beta-sheet nanofibers with left- and right-handed twists, respectively, under appropriate condition. On the other hand, the 1L/1D binary mixture was found to form only globular aggregates at the same condition. Thus, amyloid-like nanofiber formation and its nanostructure could be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
88
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 19 publications
0
88
1
1
Order By: Relevance
“…Langmuir monolayers of b-sheet peptides were, for example, reported to function as templates and serve as nuclei for the formation of inorganic nanocrystallites at the air-water interface. 12 Recently, numerous research groups have demonstrated that amphiphilic peptides self-assemble into b-sheet nanofiber architectures, [13][14][15][16][17][18][19][20] the surface of which has potential as a novel nanotemplate. [21][22][23] Several groups [24][25][26][27] have separately used b-sheet peptide nanofibers as templates to organize diacetylenes or dienes and promote their topochemical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir monolayers of b-sheet peptides were, for example, reported to function as templates and serve as nuclei for the formation of inorganic nanocrystallites at the air-water interface. 12 Recently, numerous research groups have demonstrated that amphiphilic peptides self-assemble into b-sheet nanofiber architectures, [13][14][15][16][17][18][19][20] the surface of which has potential as a novel nanotemplate. [21][22][23] Several groups [24][25][26][27] have separately used b-sheet peptide nanofibers as templates to organize diacetylenes or dienes and promote their topochemical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Langmuir monolayers of b-sheet peptides were reported to work as templates and nucleate the formation of CdS nanocrystallites at the air-water interface. 2 Recently, we demonstrated that an amphiphilic artificial peptide can self-assemble into b-sheet nanofiber architectures, [3][4][5] the surfaces of which have potential as a novel nanotemplate. 6 Stupp's group 7 and Mihara's group 8 used b-sheet peptide nanofibers with surface-binding sites as nanotemplates to accomplish the one-dimensional organization of functional materials such as gold nanoparticles and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As an attempt to fabricate peptide nanofiber architectures using self-assembling technique, our group recently focused on the amphiphilic triblock peptides such as L 4 K 8 L 4 that were found to self-assemble into well-developed nanofiber structures based on β-sheet motifs. [9][10][11] Such self-assembly of peptides into β-sheet fibrillar structures has attracted much attention because of not only their association with neurodegeneration diseases but also their potential as novel nano-scale soft-materials. From this point of view, several types of artificial peptides have been developed to produce β-sheet-based nanofibers.…”
Section: Introductionmentioning
confidence: 99%